Distribuição de mercúrio no Plâncton da Plataforma interna de Cabo Frio, Sudeste do Brasil - VELOSO, João Antônio Campos (2022)
The oceanographic upwelling phenomenon provides nutrient and trace metals replacement to surface waters that stimulates primary production. Among the metals, there is mercury, a toxic metal that can be uptake directly by phytoplankton by passive diffusion. Mercury in the environment can turn into methylmercury, a toxic compound that undergoes biomagnification. Coastal upwellings lodge large fish stocks supported by high primary production. Therefore, mercury in these regions is a direct threat to human health through ingestion of seafood. This work aims to verify if there is upwelling influence on plankton mercury bioassimilation in coastal zone. A database of nitrate concentration in water and mercury in plankton was used relative to a collection campaign carried out in three points around the island of Cabo Frio on 11/18/2015 together with meteorological data on precipitation, direction and wind speed (m / s) and surface chlorophyll data available in a COPERNICUS model linked to the European Union. In situ salinity was measured with a probe. Plankton were collected by horizontal hauls using nets with a 20and 64 μm mesh for phytoplankton and 150 and 300 μm for zooplankton. These nets were coupled to a flowmeter (General Oceanic) to obtain the volume of water filtered during each haul. Water was filtered in the laboratory on 0.45 μm filters and a nitrate determination was performed on ion chromatography (Model: Metrohm). Through the concentration of nitrate (a parameter that highlights the ACAS water mass) and with the support of wind speed and surface chlorophyll data, it was possible to identify the presence of Central South Atlantic Water (CSAW) at the point closest to the coast of Cabo Frio Island. The mercury concentration in plankton was higher at the point farthest from the shoreline and also higher in phytoplankton compared to zooplankton at all points. Thus, during the collection day, there was an influence of CSAW in one of the points with interaction in the assimilation of mercury in plankton. Therefore, the upwelling phenomenon is a direct source of mercury for the planktonic community that captures this metal and makes it bioavailable for other trophic levels. Keywords: trace-metals; biomagnification; chlorophyll-a; upwelling; southeast